COMPETITIVE STRATEGY ANALYSIS OF TOURISM (CASE STUDY IN THE MARINE TOURISM SECTOR IN NORTH MINAHASA REGENCY) - Pondaag, Jessy Jousina; Soepeno, Djurwaty; Lumintang, Genita Gracia (International Journal of Research -GRANTHAALAYAH, 2023)
This type of research is a quantitative research. The research location was carried out at the Paal Beach tourism object, which is located in Marinsow Village, East Likupang District, North Minahasa Regency. The sampling technique used purposive sampling method. Researchers took a sample of 100 respondents. Data collection methods through observation, questionnaires, and documentation. Data analysis techniques using scoring techniques, as well as SWOT analysis. The results showed that the supporting factors for the development of Paal Beach tourism objects were the attractiveness of Paal Beach tourism objects with the beautiful white sand and sea, as well as good road accessibility. Factors inhibiting development are old and lacking infrastructure such as public toilets and lodging, the absence of public transportation, and the lack of supporting facilities such as hotel communications and restaurants around tourist attractions. The tourism development strategy based on the SWOT analysis is in quadrant I, the strategy recommendations given are Progressive. The right strategy to be carried out at the Paal Beach tourism object is to maintain the beauty of the beach, increase the number of places selling souvenirs typical of the region, build basic infrastructure facilities at tourist sites and make maximum use of existing human resources and intensify promotions and build adequate and easy accessibility visitors.